2022
DOI: 10.1002/fsn3.3096
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin‐loaded cockle shell‐derived calcium carbonate nanoparticles ameliorates lead‐induced neurotoxicity in rats via attenuation of oxidative stress

Abstract: A substantial global health burden is associated with neurotoxicity caused by lead (Pb) exposure and the common mechanism of this toxicity is mainly via oxidative damage. Curcumin has remarkable pharmacological activities but remains clinically constrained due to its poor bioavailability when orally administered. Currently, cockle shell‐derived calcium carbonate nanoparticle (CSCaCO 3 NP) is gaining more acceptance in nanomedicine as a nanocarrier to various therapeutics. This study aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 116 publications
0
1
0
Order By: Relevance
“…Curcumin, characterized by the chemical formula 1,7‐bis(4‐hydroxy‐3 methoxyphenyl)‐1,6‐heptadiene‐3,5‐dione, represents the principal bioactive compound found in Curcuma longa (El‐Desoky et al., 2022 ). Evidence has shown that curcumin exhibits anti‐inflammatory, antioxidants, anti‐cancer activities (Khajeh pour et al., 2023 ; Mailafiya et al., 2023 ). These advantageous features are attributed to its elevated antioxidant activity, stemming from the hydroxyl and methylene groups within the β‐diketone moiety present in its chemical structure (Chen et al., 2023 ; Wang et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, characterized by the chemical formula 1,7‐bis(4‐hydroxy‐3 methoxyphenyl)‐1,6‐heptadiene‐3,5‐dione, represents the principal bioactive compound found in Curcuma longa (El‐Desoky et al., 2022 ). Evidence has shown that curcumin exhibits anti‐inflammatory, antioxidants, anti‐cancer activities (Khajeh pour et al., 2023 ; Mailafiya et al., 2023 ). These advantageous features are attributed to its elevated antioxidant activity, stemming from the hydroxyl and methylene groups within the β‐diketone moiety present in its chemical structure (Chen et al., 2023 ; Wang et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%